2019
DOI: 10.1002/slct.201802955
|View full text |Cite
|
Sign up to set email alerts
|

A Nickel‐Based Pectin Metal‐Organic Framework as a Hydrogen Oxidation Reaction Catalyst for Proton‐Exchange‐Membrane Fuel Cells

Abstract: Environmentally friendly non‐PGM (platinum group metal) anode catalyst made of nickel pectate, the biological raw material, was developed and tested in proton‐exchange‐membrane fuel cell (PEMFC). 5.2 mA cm‐2 and 1.5 mW cm‐2, the maximum current density and the maximum power density of the developed catalyst, respectively, correspond to sufficiently high values of these characteristics for PEMFC with an anode without a PGM catalyst and a cathode with a platinum one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Research has shown that sodium pectate with a 25% substitution of sodium ions for nickel ones can be used as ORR [ 8 ] and HOR [ 9 ] catalysts in PEMFCs as an active material in non-platinum catalytic systems. Recently, varying the concentration of Ni(II) ions in nickel complexes of sodium pectate [ 10 ] allowed researchers to find the optimal concentration of the transition metal to improve the characteristics of the studied PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that sodium pectate with a 25% substitution of sodium ions for nickel ones can be used as ORR [ 8 ] and HOR [ 9 ] catalysts in PEMFCs as an active material in non-platinum catalytic systems. Recently, varying the concentration of Ni(II) ions in nickel complexes of sodium pectate [ 10 ] allowed researchers to find the optimal concentration of the transition metal to improve the characteristics of the studied PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several scientists have been attracted by this important part of reticular chemistry [9][10][11][12], probably due to the fact that the researcher's inventiveness is the only limitation in this research field. Thus, different research groups have greatly contributed to the exponential growth of this area, using these materials in a diverse range of applications, including catalysis [13][14][15][16][17][18][19], water harvesting [20][21][22][23], biomedicine [24][25][26] and sensing [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%